Determination of the effect of carbon nanotubes on the microstructure and functional properties of polycarbonate-based polymer nanocomposite materials - Lysenkov, Eduard; Klymenko, Leonid (Eastern-European Journal of Enterprise Technologies, 2021)
Polymer nanocomposites are widely used in various high-tech industries. Due to the combination of the elasticity of the matrix and the strength of the inorganic filler, they have improved functional characteristics compared to unfilled polymers. The article is devoted to determining the effect of carbon nanotubes (CNT) on the microstructure and properties of polymeric nanocomposite materials for 3D printing based on polycarbonate. As a result of this work, a series of composite materials was manufactured using a piston extruder. Their microstructure and functional characteristics were investigated using methods of optical microscopy, thermophysical, electrical and mechanical analysis. It was found that CNTs form clusters in the polymer matrix, which form a percolation network at a content of 0.5–0.8 %. This feature of the structure formation of CNTs provided an abrupt increase in the functional characteristics of the materials obtained. It is shown that with an increase in the filler content in the system to 3 %, the thermal conductivity rapidly increases to 1.22 W/(m∙K). A similar effect is observed for the electrical conductivity, which increases by seven orders of magnitude from 10-12 to 10-5 S/cm at 3 % CNT content in the system, exhibiting percolation behavior. With the introduction of CNTs, the crystallinity degree of the polymer matrix decreases by almost 15 %, due to the fact that the developed surface of the nanotubes creates steric hindrances for polycarbonate macromolecules. This effect almost negates the reinforcing effect of nanotubes; therefore, the mechanical tensile strength with the introduction of 3 % CNTs increases by only 21 % compared to the unfilled matrix. In terms of their functional characteristics, the obtained materials are promising for the creation of filaments for 3D printing on their basis.